PENGARUH KINERJA PERUSAHAAN, GOOD CORPORATE GOVERNANCE (GCG), DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Sektor Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Yani Marliza; Darsono Darsono (Diponegoro Journal of Accounting, 2025)
This study aims to test hypotheses and generate empirical findings regarding the influence of firm performance, Good Corporate Governance (GCG), and audit quality on tax avoidance, which is proxied by the Effective Tax Rate (ETR). Firm performance is measured using two indicators, firm size and profitability, while Good Corporate Governance (GCG) is measured by the proportion of independent commissioners. The research employs a secondary data observation method. The data were obtained from industrial sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2023. Data collection was carried out through observation of annual reports retrieved from the companies' official websites, while financial reports were sourced from Bloomberg FEB Undip. The sampling technique used is purposive sampling, which involves selecting samples based on specific criteria, resulting in 146 observational data points. The data analysis technique used in this study is multiple linear regression analysis.The results show that profitability has a negative and significant effect on tax avoidance, while firm size, the proportion of independent commissioners, and audit quality have no significant effect on tax avoidance.